A Comparison of Diving Behavior of Goose‐Beaked and Dense‐Beaked Whales From Tagging Studies in Multiple Ocean Basins - Jay Barlow; Robin W. Baird; Janelle Badger; Gregory S. Schorr; Erin A. Falcone; Shannon N. Coates; Peter L. Tyack; Andrew J. Read; Leigh S. Hickmott; John W. Durban; Diane Claridge; Natacha Aguilar de Soto; et al. (Marine Mammal Science, 2026)
Studies of cetacean diving behavior in multiple locations in different ocean basins allow for an assessment of variability within and among populations. We examine foraging dive behaviors of goose‐beaked whales ( Ziphius cavirostris ) and dense‐beaked whales ( Mesoplodon densirostris ) using data from 132 tagged whales in seven locations in the Pacific and Atlantic Oceans and the Mediterranean Sea. Acoustic recording tags are used to identify foraging dives by the presence of echolocation. For other tag types, foraging dives are identified based on maximum dive depth. Five parameters are used to characterize foraging dives: maximum dive depth, foraging dive duration, dive cycle duration, and the mean and standard deviation of echolocation depths. We find that differences among dives within one tagged individual are typically larger than the differences among individuals or among locations, and that differences among individuals are typically similar in magnitude to differences among locations. Regression is used to estimate the mean and standard deviation of echolocation depths from maximum dive depth for dives without acoustic data. Composite values of foraging dive parameters (and standard deviations) are estimated as the average of all study locations.

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Evaluation of an open-source nutrient delivery model for estimating pesticide loads in river catchments - Emily V. Upcott; Virginie Keller; Daniel S. Read; Clarissa Rizzo; Jude Jeans; John W. Redhead (Science of The Total Environment, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of interactive effects on long‐term population trajectories in multispecies reintroductions - Katherine E. Moseby; John L. Read; Katherine Tuft; Leanne K. Van der Weyde (Conservation Biology, 2024)
Reintroduced populations are typically considered to progress through establishment, growth, and regulatory phases. However, most reintroduction programs do not monitor intensively enough to test this conceptual model. We studied population indices derived from track activity of 4 threatened species (greater bilby [ Macrotis lagotis ], burrowing bettong [ Bettongia lesueur ], greater stick‐nest rat [ Leporillus conditor ], and Shark Bay bandicoot [ Perameles bougainville ]) over 23 years after multiple reintroductions of each species in arid Australia. We compared population trajectories among species and investigated the effect of time and environmental variables. All species bred immediately after release, and the growth phase lasted 3–16 years, varying markedly among but not within species. The end of the growth phase was characterized by an obvious peak in population density followed by either a catastrophic decline and sustained low density (bettongs), a slow decline to extirpation after 20 years (stick‐nest rat), or a slight decline followed by irregular fluctuations (bilby and bandicoot). Minor fluctuations were related to environmental variables, including 12‐month cumulative rainfall and lagged summer maximum temperatures. Three of the 4 species did not reach a regulation phase, even after 23 years, possibly due to interspecific competition and trophic cascades triggered by predator removal and multispecies reintroductions. Bilbies and bandicoots exhibited a second growth phase 18 years after reintroduction, likely caused by high rainfall and increased resources following the population crash of overabundant bettongs. Our results suggest that assemblages within multispecies reintroductions demonstrate high variability in population trajectories due to interactive effects. Intensive monitoring to assess population viability may require decades, particularly where multiple species are reintroduced, release sites are confined, and the climate is unpredictable. Intensive monitoring also allows for adaptive management to prevent precipitous population declines. Practitioners should not assume reintroduced species pass through predictable postrelease population phases or that viability is assured after a certain period.

Depositional and tectonic influences on preservation of Milankovitch record during long-term global cooling: Middle and Upper Ordovician convergent foreland, eastern USA - J. Fred Read; Michael C. Pope; Maya Elrick; Linda Hinnov; John Repetski; Robert T. Ryder; Douglas G. Patchen; Richard Diecchio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Havens are a pathway, not an endpoint, for species recovery: A response to Woinarski et al. (2023) - John L. Read; Kev Bradley; Iain J. Gordon; Adrian D. Manning; Linda E. Neaves; April E. Reside; Kiarrah J. Smith; Rick Southgate; Adrian F. Wayne; Andrew R. Weeks; Belinda A. Wilson; Katherine E. Moseby (Biological Conservation, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Correction to: Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

The Influence of Biological Maturity on Dynamic Force–Time Variables and Vaulting Performance in Young Female Gymnasts - Sylvia Moeskops; Jon L. Oliver; Paul J. Read; John B. Cronin; Gregory D. Myer; G. Gregory Haff; Isabel S. Moore; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2020)
Purpose This cross-sectional study investigated dynamic force–time variables and vaulting performance in young female gymnasts of different maturity status. Methods 120 gymnasts aged 5–14 years were sub-divided into maturity groupings using percent of predicted adult height (%PAH) attained. Participants performed three jumping protocols, the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ), before completing straight jump vaults that were recorded using two-dimensional video. Results Jumping performance improved with biological maturity evidenced by the most mature gymnasts’ producing significantly more absolute force ( P < 0.05; all d > 0.78), impulse ( P < 0.05; all d > 0.75) and power ( P < 0.05; all d > 0.91) than the least mature group, resulting in the greater jump heights ( P < 0.05; all d > 0.70). While, no significant differences were observed in relative peak force across multiple tests, measures of relative peak power did significantly increase with maturity. Based upon regression analyses, maturation was found to influence vertical take-off velocity during vaulting, explaining 41% of the variance in each jumping protocol. Across all tests, the DJ was found to have the highest predictive ability of vaulting vertical take-off velocity, explaining 55% of the total variance. Conclusion Biological maturation impacts jump height and underpinning mechanical variables in young female gymnasts. Vaulting vertical take-off velocity appears to be influenced by maturation and various dynamic force–time variables, particularly those during DJ, which had the highest explained total variance.

Metaviromic analysis reveals coinfection of papaya in western Kenya with a unique strain of Moroccan watermelon mosaic virus and a novel member of the family Alphaflexiviridae - David Alan Read; John Muoma; Genevieve Dawn Thompson (Archives of Virology, 2020)

Beyond counts and averages: Relating geodiversity to dimensions of biodiversity - Quentin D. Read; Phoebe L. Zarnetske; Sydne Record; Kyla M. Dahlin; Jennifer K. Costanza; Andrew O. Finley; Keith D. Gaddis; John M. Grady; Martina L. Hobi; Andrew M. Latimer; Sparkle L. Malone; Scott V. Ollinger; et al. (Global Ecology and Biogeography, 2020)
Aim We may be able to buffer biodiversity against the effects of ongoing climate change by prioritizing the protection of habitat with diverse physical features (high geodiversity) associated with ecological and evolutionary mechanisms that maintain high biodiversity. Nonetheless, the relationships between biodiversity and habitat vary with spatial and biological context. In this study, we compare how well habitat geodiversity (spatial variation in abiotic processes and features) and climate explain biodiversity patterns of birds and trees. We also evaluate the consistency of biodiversity–geodiversity relationships across ecoregions. Location Contiguous USA. Time period 2007–2016. Taxa studied Birds and trees. Methods We quantified geodiversity with remotely sensed data and generated biodiversity maps from the Forest Inventory and Analysis and Breeding Bird Survey datasets. We fitted multivariate regressions to alpha, beta and gamma diversity, accounting for spatial autocorrelation among Nature Conservancy ecoregions and relationships among taxonomic, phylogenetic and functional biodiversity. We fitted models including climate alone (temperature and precipitation), geodiversity alone (topography, soil and geology) and climate plus geodiversity. Results A combination of geodiversity and climate predictor variables fitted most forms of bird and tree biodiversity with Main conclusions Although climatic predictors tended to have larger individual effects than geodiversity, adding geodiversity improved climate‐only models of biodiversity. Geodiversity was correlated with biodiversity more consistently than with climate across ecoregions, but models tended to have a poor fit in ecoregions held out of the training dataset. Patterns of geodiversity could help to prioritize conservation efforts within ecoregions. However, we need to understand the underlying mechanisms more fully before we can build models transferable across ecoregions.

Exploring the internal and external wildlife gradients created by conservation fences - Katherine E. Moseby; Hugh McGregor; Brydie M. Hill; John L. Read (Conservation Biology, 2020)
Spillover effects are an expansion of conservation benefits beyond protected areas through dispersal of species that reside within. They have been well documented in marine but not terrestrial systems. To understand the effects on wildlife created by conservation fences, we explored the internal and external gradients of activity in mammal, reptile, and bird species at a conservation reserve in arid Australia that is fenced to exclude invasive rabbits ( Oryctolagus cuniculus ), cats ( Felis catus ), and foxes ( Vulpes vulpes ). Two methods were used: counts of animal tracks along transects on sand dunes and captures at pitfall‐trapping sites. In both cases, sites were spaced at different distances from the reserve fenceline inside and outside the reserve. We recorded a range of spillover, source‐sink, step, and barrier effects that combined to create a zone within and around the reserve with fence‐induced species‐specific wildlife gradients. Two endemic rodents but none of the 4 mammal species reintroduced to the reserve showed positive spillover effects. Barrier effects, where activity was highest close to the fence, were recorded for the feral cat and native bettong ( Bettongia lesueur ), species that could not breach the fence. In comparison, some reptiles and native mammal species that could permeate the fence displayed source‐sink effects; that is, their activity levels were reduced close to the fence likely due to constant emigration to the side with lower density. Activity of some reptiles was lowest at sites inside the reserve and gradually increased at outside sites with distance from the fence, a gradient likely related to trophic cascades triggered by predator exclusion. Our result shows that fenced reserves can create overlapping layers of species‐specific gradients related to each species’ ability to permeate the fence and its varying susceptibility to threats. Managers should be aware that these gradients may extend for several kilometers either side of the fence and that not all contained species will increase in abundance. Creating wider conservation benefits may require increased fence permeability and threat reduction outside the fence.

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Persistence through tough times: fixed and shifting refuges in threatened species conservation - April E. Reside; Natalie J. Briscoe; Chris R. Dickman; Aaron C. Greenville; Bronwyn A. Hradsky; Salit Kark; Michael R. Kearney; Alex S. Kutt; Dale G. Nimmo; Chris R. Pavey; John L. Read; Euan G. Ritchie; et al. (Biodiversity and Conservation, 2019)

Towards connecting biodiversity and geodiversity across scales with satellite remote sensing - Phoebe L. Zarnetske; Quentin D. Read; Sydne Record; Keith D. Gaddis; Stephanie Pau; Martina L. Hobi; Sparkle L. Malone; Jennifer Costanza; Kyla M. Dahlin; Andrew M. Latimer; Adam M. Wilson; John M. Grady; et al. (Global Ecology and Biogeography, 2019)
Issue Geodiversity (i.e., the variation in Earth's abiotic processes and features) has strong effects on biodiversity patterns. However, major gaps remain in our understanding of how relationships between biodiversity and geodiversity vary over space and time. Biodiversity data are globally sparse and concentrated in particular regions. In contrast, many forms of geodiversity can be measured continuously across the globe with satellite remote sensing. Satellite remote sensing directly measures environmental variables with grain sizes as small as tens of metres and can therefore elucidate biodiversity–geodiversity relationships across scales. Evidence We show how one important geodiversity variable, elevation, relates to alpha, beta and gamma taxonomic diversity of trees across spatial scales. We use elevation from NASA's Shuttle Radar Topography Mission (SRTM) and c . 16,000 Forest Inventory and Analysis plots to quantify spatial scaling relationships between biodiversity and geodiversity with generalized linear models (for alpha and gamma diversity) and beta regression (for beta diversity) across five spatial grains ranging from 5 to 100 km. We illustrate different relationships depending on the form of diversity; beta and gamma diversity show the strongest relationship with variation in elevation. Conclusion With the onset of climate change, it is more important than ever to examine geodiversity for its potential to foster biodiversity. Widely available satellite remotely sensed geodiversity data offer an important and expanding suite of measurements for understanding and predicting changes in different forms of biodiversity across scales. Interdisciplinary research teams spanning biodiversity, geoscience and remote sensing are well poised to advance understanding of biodiversity–geodiversity relationships across scales and guide the conservation of nature.

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

Pond and Irrigation Model (PIM): a Tool for Simultaneously Evaluating Pond Water Availability and Crop Irrigation Demand - Ying Ouyang; Gary Feng; Theodor D. Leininger; John Read; Johnie N. Jenkins (Water Resources Management, 2018)

Consistently inconsistent drivers of microbial diversity and abundance at macroecological scales - John Nicholas Hendershot; Quentin D. Read; Jeremiah A. Henning; Nathan J. Sanders; Aimée T. Classen (Ecology, 2017)
Macroecology seeks to understand broad‐scale patterns in the diversity and abundance of organisms, but macroecologists typically study aboveground macroorganisms. Belowground organisms regulate numerous ecosystem functions, yet we lack understanding of what drives their diversity. Here, we examine the controls on belowground diversity along latitudinal and elevational gradients. We performed a global meta‐analysis of 325 soil communities across 20 studies conducted along temperature and soil pH gradients. Belowground taxa, whether bacterial or fungal, observed along a given gradient of temperature or soil pH were equally likely to show a linear increase, linear decrease, humped pattern, trough‐shaped pattern, or no pattern in diversity along the gradient. Land‐use intensity weakly affected the diversity‐temperature relationship, but no other factor did so. Our study highlights disparities among diversity patterns of soil microbial communities. Belowground diversity may be controlled by the associated climatic and historical contexts of particular gradients, by factors not typically measured in community‐level studies, or by processes operating at scales that do not match the temporal and spatial scales under study. Because these organisms are responsible for a suite of key processes, understanding the drivers of their distribution and diversity is fundamental to understanding the functioning of ecosystems.

A Model to Estimate Hydrological Processes and Water Budget in an Irrigation Farm Pond - Ying Ouyang; Joel O. Paz; Gary Feng; John J. Read; Ardeshir Adeli; Johnie N. Jenkins (Water Resources Management, 2017)

The linkage between stratospheric water vapor and surface temperature in an observation-constrained coupled general circulation model - Yuan Wang; Hui Su; Jonathan H. Jiang; Nathaniel J. Livesey; Michelle L. Santee; Lucien Froidevaux; William G. Read; John Anderson (Climate Dynamics, 2017)

Rabbit biocontrol and landscape‐scale recovery of threatened desert mammals - Reece D. Pedler; Robert Brandle; John L. Read; Richard Southgate; Peter Bird; Katherine E. Moseby (Conservation Biology, 2016)
Funding for species conservation is insufficient to meet the current challenges facing global biodiversity, yet many programs use expensive single‐species recovery actions and neglect broader management that addresses threatening processes. Arid Australia has the world's worst modern mammalian extinction record, largely attributable to competition from introduced herbivores, particularly European rabbits ( Oryctolagus cuniculus ) and predation by feral cats ( Felis catus ) and foxes ( Vulpes vulpes ). The biological control agent rabbit hemorrhagic disease virus (RHDV) was introduced to Australia in 1995 and resulted in dramatic, widespread rabbit suppression. We compared the area of occupancy and extent of occurrence of 4 extant species of small mammals before and after RHDV outbreak, relative to rainfall, sampling effort, and rabbit and predator populations. Despite low rainfall during the first 14 years after RHDV, 2 native rodents listed by the International Union for Conservation of Nature (IUCN), the dusky hopping‐mouse ( Notomys fuscus ) and plains mouse ( Pseudomys australis ), increased their extent of occurrence by 241–365%. A threatened marsupial micropredator, the crest‐tailed mulgara ( Dasycercus cristicauda ), underwent a 70‐fold increase in extent of occurrence and a 20‐fold increase in area of occupancy. Both bottom‐up and top‐down trophic effects were attributed to RHDV, namely decreased competition for food resources and declines in rabbit‐dependent predators. Based on these sustained increases, these 3 previously threatened species now qualify for threat‐category downgrading on the IUCN Red List. These recoveries are on a scale rarely documented in mammals and give impetus to programs aimed at targeted use of RHDV in Australia, rather than simply employing top‐down threat‐based management of arid ecosystems. Conservation programs that take big‐picture approaches to addressing threatening processes over large spatial scales should be prioritized to maximize return from scarce conservation funding. Further, these should be coupled with long‐term ecological monitoring, a critical tool in detecting and understanding complex ecosystem change.

Association of poor sleep with behavior and quality of life in children and adolescents with cystic fibrosis - Keith Cavanaugh; Lisa Read; Jill Dreyfus; Mahrya Johnson; John McNamara (Sleep and Biological Rhythms, 2016)

The effect of anthropogenic arsenic contamination on the earthworm microbiome - Daniel Antony Pass; Andrew John Morgan; Daniel S. Read; Dawn Field; Andrew J. Weightman; Peter Kille (Environmental Microbiology, 2015)
Summary Earthworms are globally distributed and perform essential roles for soil health and microbial structure. We have investigated the effect of an anthropogenic contamination gradient on the bacterial community of the keystone ecological species L umbricus rubellus through utilizing 16 S rRNA pyrosequencing for the first time to establish the microbiome of the host and surrounding soil. The earthworm‐associated microbiome differs from the surrounding environment which appears to be a result of both filtering and stimulation likely linked to the altered environment associated with the gut micro‐habitat (neutral pH , anoxia and increased carbon substrates). We identified a core earthworm community comprising P roteobacteria (∼50%) and A ctinobacteria (∼30%), with lower abundances of B acteroidetes (∼6%) and A cidobacteria (∼3%). In addition to the known earthworm symbiont ( V erminephrobacter sp.), we identified a potential host‐associated G ammaproteobacteria species ( S erratia sp.) that was absent from soil yet observed in most earthworms. Although a distinct bacterial community defines these earthworms, clear family‐ and species‐level modification were observed along an arsenic and iron contamination gradient. Several taxa observed in uncontaminated control microbiomes are suppressed by metal/metalloid field exposure, including eradication of the hereto ubiquitously associated V erminephrobacter symbiont, which raises implications to its functional role in the earthworm microbiome.

Analytical approaches to support current understanding of exposure, uptake and distributions of engineered nanoparticles by aquatic and terrestrial organisms - Carolin Schultz; Kate Powell; Alison Crossley; Kerstin Jurkschat; Peter Kille; A. John Morgan; Daniel Read; William Tyne; Elma Lahive; Claus Svendsen; David J. Spurgeon (Ecotoxicology, 2015)

Recommendations for photo‐identification methods used in capture‐recapture models with cetaceans - Kim Urian; Antoinette Gorgone; Andrew Read; Brian Balmer; Randall S. Wells; Per Berggren; John Durban; Tomoharu Eguchi; William Rayment; Philip S. Hammond (Marine Mammal Science, 2015)
Capture‐recapture methods are frequently employed to estimate abundance of cetaceans using photographic techniques and a variety of statistical models. However, there are many unresolved issues regarding the selection and manipulation of images that can potentially impose bias on resulting estimates. To examine the potential impact of these issues we circulated a test data set of dorsal fin images from bottlenose dolphins to several independent research groups. Photo‐identification methods were generally similar, but the selection, scoring, and matching of images varied greatly amongst groups. Based on these results we make the following recommendations. Researchers should: (1) determine the degree of marking, or level of distinctiveness, and use images of sufficient quality to recognize animals of that level of distinctiveness; (2) ensure that markings are sufficiently distinct to eliminate the potential for “twins” to occur; (3) stratify data sets by distinctiveness and generate a series of abundance estimates to investigate the influence of including animals of varying degrees of markings; and (4) strive to examine and incorporate variability among analysts into capture‐recapture estimation. In this paper we summarize these potential sources of bias and provide recommendations for best practices for using natural markings in a capture‐recapture framework.

Prevalence of enterotoxigenic Escherichia coli virulence genes from scouring piglets in Zimbabwe - Evelyn Madoroba; Edilbert Van Driessche; Henri De Greve; Jan Mast; Ignatious Ncube; John Read; Sonia Beeckmans (Tropical Animal Health and Production, 2009)

Phosphylated tyrosine in albumin as a biomarker of exposure to organophosphorus nerve agents - Nichola H. Williams; John M. Harrison; Robert W. Read; Robin M. Black (Archives of Toxicology, 2007)

Comparative spatial and temporal localisation of perlecan, aggrecan and type I, II and IV collagen in the ovine meniscus: an ageing study - James Melrose; Susan Smith; Martin Cake; Richard Read; John Whitelock (Histochemistry and Cell Biology, 2005)

Perlecan displays variable spatial and temporal immunolocalisation patterns in the articular and growth plate cartilages of the ovine stifle joint - James Melrose; Susan Smith; Martin Cake; Richard Read; John Whitelock (Histochemistry and Cell Biology, 2005)

Molecular and cytological characterization of a cytoplasmic-specific mutant in pima cotton (Gossypium barbadense L.) - Mehmet Karaca; Sukumar Saha; Franklin E. Callahan; Johnie N. Jenkins; John J. Read; Richard G. Percy (Euphytica, 2004)

REPRODUCTIVE SEASONALITY OF WESTERN ATLANTIC BOTTLENOSE DOLPHINS OFF NORTH CAROLINA, U.S.A. - Victoria G. Thayer; Andrew J. Read; Ari S. Friedlaender; David R. Colby; Aleta A. Hohn; William A. McLellan; D. Ann Pabst; Jennifer L. Dearolf; Nan I. Bowles; John R. Russell; Keith A. Rittmaster (Marine Mammal Science, 2003)
A bstract We describe reproductive seasonality of bottlenose dolphins in North Carolina (NC), U.S.A., using strandings data from the entire coast of NC and sighting data from Beaufort, NC and by estimating dates of birth of known females. We found a strong peak of neonate strandings in the spring (April‐May), and low levels of neonate strandings in the fall and winter. The distribution of neonate strandings was significantly different from a uniform distribution ( P K = 3.8). We found a unimodal distribution of 282 sightings of neonates with a diffuse peak in the summer. The temporal distribution of sightings of neonates departed significantly from a uniform distribution (P K = 5.1). Estimated birth dates of neonates from known females occurred in May ( n = 6) and June ( n = 4), with a single fall birth. These methods shed light on bottlenose reproductive patterns and underscore the value of using information from multiple types of data. Clarification of bottlenose dolphin reproductive patterns, such as the seasonality of birth, may enhance our understanding of the population structure of this species in the mid‐Atlantic region.

Effects of enhanced nitrogen deposition and phosphorus limitation on nitrogen budgets of semi‐natural grasslands - Gareth K. Phoenix; Rosemary E. Booth; Jonathan R. Leake; David J. Read; J. Philip Grime; John A. Lee (Global Change Biology, 2003)
Increased reactive atmospheric N deposition has been implicated in floristic changes in species‐rich acidic and calcareous grasslands, but the fate of this pollutant N in these ecosystems is unknown. This paper reports the first analysis of N budgets and N fluxes for two grasslands in the White Peak area of Derbyshire, one of the most heavily N‐polluted locations in the UK. N fluxes were monitored in lysimeter cores (retaining the original turfs) taken from field plots of unimproved acidic and calcareous grasslands that had received (in addition to ambient N deposition) simulated enhanced N deposition treatments of 3.5 and 14 g N m −2 yr −1 for 6 years. The influence of reducing phosphorus limitation was assessed by factorial additions of P. Seasonal leached losses of nitrate, ammonia and organic N were monitored in detail along with estimates of N removal through simulated grazing and gaseous losses through denitrification and volatilization. The rates of N fluxes by these pathways were used to create N budgets for the grasslands. Both grasslands were found to be accumulating much of the simulated additional N deposition: up to 89% accumulated in the calcareous grassland and up to 38% accumulated in the acidic grassland. The major fluxes of N loss from these grasslands were by simulated grazing and leaching of soluble organic N (constituting 90% of leached N under ambient conditions). Leached inorganic N (mainly nitrate) contributed significantly to the output flux of N under the highest N treatment only. Loss of N through ammonia volatilization accounted for less than 6% of the N added as simulated deposition, while denitrification contributed significantly to output fluxes only in the acidic grassland during winter. The implications of the results for ecosystem N balances and the likely consequences of N accumulation on these grasslands are discussed.

Evaluation in barley lines of a simple pollen method for breeding for drought tolerance in wheat - James M. Morgan; John F. Holland; Barbara J. Read (Cereal Research Communications, 2002)

The interaction of sarin and soman with plasma proteins: the identification of a novel phosphonylation site - Robin M. Black; John M. Harrison; Robert W. Read (Archives of Toxicology, 1999)

Ecological and Toxicological Effects of Exposure to an Acidic, Radioactive Tailings Storage - John Read; Robyn Pickering (Environmental Monitoring and Assessment, 1999)